2013
DOI: 10.1111/cfs.12030
|View full text |Cite
|
Sign up to set email alerts
|

‘Other children say you're not normal because you don't live with your parents’. Children's views of living with informal kinship carers: social networks, stigma and attachment to carers

Abstract: Our re‐analysis of census data shows that 95% of kinship arrangements are ‘informal’, i.e. made outside the formal child welfare system. Interviews with 80 children aged 8–18 years in informal kinship care and their carers showed that most children were well attached to their kin carers, but one‐third had been taunted or bullied because they did not live with their parents. Many children tightly controlled who knew about this potentially stigmatizing information. Most children had good numbers of adults and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…Further, adolescents living in RYC might feel that they fail to attain the social norm of normal family life. Children and adolescents may be stigmatized because they do not live with their parents [52]. Self-conscious emotions including shame and guilt [19] and feeling different than others might be dominating when adolescents in RYC institutions evaluate their QoL.…”
Section: Social Acceptance and Qolmentioning
confidence: 99%
“…Further, adolescents living in RYC might feel that they fail to attain the social norm of normal family life. Children and adolescents may be stigmatized because they do not live with their parents [52]. Self-conscious emotions including shame and guilt [19] and feeling different than others might be dominating when adolescents in RYC institutions evaluate their QoL.…”
Section: Social Acceptance and Qolmentioning
confidence: 99%
“…Strengthening positive skills and behaviors early in development can have what Spoth and colleagues (2009) refer to as a “shielding effect” by preventing risks for becoming exposed to or involved in later negative behaviors. Such programs may also be more accessible to children in foster care and their foster caregivers, who already face stigma for their involvement with the child welfare system and thus might avoid problem-focused programs for fear of further stigmatization (Blythe, Jackson, Halcomb, & Wilkes, 2012; Farmer, Selwyn, & Meakings, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The high numbers of carers and children described as living in poverty, in both the UK and US studies (Chase Goodman et al, 2004;Selwyn and Nandy, 2012;Farmer et al, 2013), were partly associated with the sizeable proportion of single, female carers (McLean and Thomas, 1996;Bunch et al, 2007;Sheran and Swann, 2007;Gleeson et al, 2009;Davis-Sowers, 2012;Stokes, 2014), and grandparent carers whose average age ranged from 60 years (Letiecq et al, 2008b) to 47.5 years (Washington et al, 2013).…”
Section: Povertymentioning
confidence: 99%
“…For example, Minkler and Fuller-Thompson's (2005) analysis of US census data, reported that 31.6% of the grandparent carers lived below the poverty line. Moreover, carers reported financial difficulties as being their paramount concern (McKenzie et al, 2010; Backhouse and Graham, 2012;Farmer et al, 2013), with some struggling to meet the child's basic needs (Swann and Sylvester, 2006). Comparative studies reported that informal carers were more likely to be living on very low incomes, or have experienced major financial difficulties, compared with their counterparts providing care under formal arrangements (Swann and Sylvester, 2006;Strozier and Krisman, 2007;Harnett et al, 2014).…”
Section: Povertymentioning
confidence: 99%